Genetic diversity of sago palm in Indonesia based on chloroplast DNA (cpDNA) markers - BARAHIMA ABBAS; YANUARIUS RENWARIN; MUHAMMAD HASIM BINTORO; SUDARSONO SUDARSONO; MEMEN SURAHMAN2; HIROSHI EHARA (Biodiversitas Journal of Biological Diversity, 2010)
Abbas B, Renwarin Y, Bintoro MH, Sudarsono, Surahman M, Ehara H (2010) Genetic diversity of sago palm in Indonesia based on chloroplast DNA (cpDNA) markers. Biodiversitas 11: 112-117. Sago palm (Metroxylon sagu Rottb.) was believed capable to accumulate high carbohydrate content in its trunk. The capability of sago palm producing high carbohydrate should be an appropriate criterion for defining alternative crops in anticipating food crisis. The objective of this research was to study genetic diversity of sago palm in Indonesia based on cpDNA markers. Total genome extraction was done following the Qiagen DNA isolation protocols 2003. Single Nucleotide Fragments (SNF) analyses were performed by using ABI Prism GeneScanR 3.7. SNF analyses detected polymorphism revealing eleven alleles and ten haplotypes from total 97 individual samples of sago palm. Specific haplotypes were found in thepopulation from Papua, Sulawesi, and Kalimantan. Therefore, the three islands will be considered as origin of sago palm diversities in Indonesia. The highest haplotype numbers and the highest specific haplotypes were found in the population from Papua suggesting this islands as the centre and the origin of sago palm diversities in Indonesia. The research had however no sufficient data yet to conclude the Papua origin of sago palm. Genetic hierarchies and differentiations of sago palm samples were observed significantly different within populations (P=0.04574), among populations (P=0.04772), and among populations within the island (P=0.03366), but amongislands no significant differentiations were observed (P= 0.63069).Key words: genetic diversity, sago palm, chloroplast DNA, haplotype, Indonesia.